2004
DOI: 10.1515/jpem.2004.17.11.1527
|View full text |Cite
|
Sign up to set email alerts
|

Breast-fed Infants have Higher Leptin Values than Formula-fed Infants in the First Four Months of Life

Abstract: The kind of feeding might be a factor affecting serum leptin concentration in term infants. The long-term consequences of this difference between BF and FF infants and leptin's role in promoting obesity later in life are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 21 publications
7
15
1
Order By: Relevance
“…The effect of feeding mode on leptin levels in infancy is contradictory, as studies have shown higher (25), equal (26), and lower (27) leptin levels in formula-fed compared to breast-fed infants during the first 4 mo of life. One possible explanation for the different findings may be different patterns of leptin concentrations by age for breast-fed and formula-fed infants during the first 6 mo (26).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of feeding mode on leptin levels in infancy is contradictory, as studies have shown higher (25), equal (26), and lower (27) leptin levels in formula-fed compared to breast-fed infants during the first 4 mo of life. One possible explanation for the different findings may be different patterns of leptin concentrations by age for breast-fed and formula-fed infants during the first 6 mo (26).…”
Section: Discussionmentioning
confidence: 99%
“…31 Higher levels of serum leptin are detected in breast-fed than in bottle-fed infants during the first years of life. 32,33 Leptin acts on the hypothalamus to inhibit food intake and in turn control body weight. 34 Serum leptin levels have been reported to be inversely related to weight gain in infancy.…”
Section: Discussionmentioning
confidence: 99%
“…The hormones leptin and ghrelin are involved in regulating food intake, energy homeostasis, and body weight. Leptin levels have been reported to be higher for breastfed than formula-fed infants in one (70) but not another (71) study. The circulating leptin levels were not only related to adipose tissue production, but may be contributed from human milk (70).…”
Section: Breastfeeding and Early Neonatal Growthmentioning
confidence: 91%
“…Leptin levels have been reported to be higher for breastfed than formula-fed infants in one (70) but not another (71) study. The circulating leptin levels were not only related to adipose tissue production, but may be contributed from human milk (70). Because ghrelin stimulates insulin secretion and body fat accretion in animals (72), higher ghrelin levels in formula-fed than breastfed infants (73) may influence early weight gain (74).…”
Section: Breastfeeding and Early Neonatal Growthmentioning
confidence: 91%